Text-to-Image Generator Web Application Using React.js and Node.js for Dynamic Image Creation and Storage - Rauf, Pervez; Khan, Md Wasim; Shafi, Md Abar; Sahil, Md; Shamim, Md Shahbaz (International Journal of Innovative Research in Computer Science and Technology, 2025)
The field of generative artificial intelligence has experienced tremendous growth with the advent of deep learning-based text-to-image models, revolutionizing how machines interpret and visualize human language. This paper presents a comprehensive overview of a full-stack web-based application designed to harness this technology for practical and creative use. The application tries facilitating the generation of images from text descriptions by integrating frontend and backend technologies offering a smooth user experience and efficient performance. The system features a robust frontend built with React.js, enabling a dynamic and responsive user interface that supports real-time interactions. Tailwind CSS is well-used to ensure a consistent, mobile-first design framework that adapts onto various screen sizes and devices. On the backend, the application utilizes Node.js with the Express.js framework to look on server-side logic, route handling, and communication with external services. RESTful APIs bridge the frontend and backend, allowing clean and scalable request handling between the client and the server. For media management, the application incorporates Multer, a middleware for handling multipart/form-data, which is primarily used for uploading files. This enables users not only to generate new images from text prompts but also to upload existing images for display or further analysis. A gallery interface is provided, allowing users to browse previously generated content, encouraging exploration, creativity, and reuse of past results. Central to the system is the integration of a pre-trained deep learning-based image generation model, capable of translating natural language prompts into high-quality, photorealistic, or stylized images. This model leverages state-of-the-art transformer architectures and diffusion techniques, ensuring accuracy and fidelity in the visual output. The system supports a variety of prompt types, including descriptive, abstract, and conceptual input, expanding its applicability across domains such as art, education, entertainment, and marketing. Extensive testing and evaluation of the platform confirm its effectiveness in delivering real-time image generation with low latency and minimal resource overhead. The application also demonstrates strong user interactivity features, such as prompt history, loading indicators, and error handling for invalid input. Backend optimizations and asynchronous data handling ensure that large image files are processed efficiently without degrading the user experience.